2022
DOI: 10.1097/md.0000000000030614
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and geographic distribution of hepatocellular carcinoma in Brazil: An ecological study

Abstract: The incidence of hepatocellular carcinoma (HCC) is increasing globally, and HCC is the fourth leading cause of cancer-related death. This ecological study aimed to investigate the time trends and geographic distribution of HCC in Brazil. Data from the Brazilian Health Public System were retrospectively collected from January 2005 to December 2018. Hospitalization and intrahospital lethality rates for HCC were stratified by age and sex. Hospitalization rates and associated lethality per 100,000 inhabitants in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…As obesity, diabetes, and the associated metabolic syndrome have become highly prevalent, nonalcoholic fatty liver disease is considered one of the most common causes of chronic liver diseases and a relevant cause of HCC [ 48 ]. Developing nations face a peculiar challenge, as the industrialization process influences the socioeconomic environment, and lifestyle changes are noticed, favoring a high-caloric Westernized diet and increasing the rates of obesity and diabetes [ 49 ]. The high male prevalence of HCC can be attributed to exposure to risk factors, such as viral hepatitis, alcohol abuse, cigarette smoking, and elevated iron storage [ 50 ].…”
Section: Epidemiology Of the Major Gastrointestinal Cancersmentioning
confidence: 99%
“…As obesity, diabetes, and the associated metabolic syndrome have become highly prevalent, nonalcoholic fatty liver disease is considered one of the most common causes of chronic liver diseases and a relevant cause of HCC [ 48 ]. Developing nations face a peculiar challenge, as the industrialization process influences the socioeconomic environment, and lifestyle changes are noticed, favoring a high-caloric Westernized diet and increasing the rates of obesity and diabetes [ 49 ]. The high male prevalence of HCC can be attributed to exposure to risk factors, such as viral hepatitis, alcohol abuse, cigarette smoking, and elevated iron storage [ 50 ].…”
Section: Epidemiology Of the Major Gastrointestinal Cancersmentioning
confidence: 99%
“…5 Another study also showed that the southern region of Brazil has a proportionally higher incidence of HCC, probably because of the aging population, higher prevalence of HCV infection, and better diagnostic facilities. 6 Balbi et al 7 collected retrospective data from the Brazilian Health Public System from 2005 to 2018. HCC hospitalizations per 100,000 inhabitants were high in the South and Southeast.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the lethality rate was high in the North. 7 According to the National Institute of Cancer, there are 317 health units able to provide cancer care in Brazil; however, the geographic distribution is heterogeneous, as well as the availability of specific technologies between them, such as radiotherapy (RT), high-complexity surgeries, and image-guided procedures. For example, only 17 cancer units in the North region comprise approximately 8.5% of the Brazilian population.…”
Section: Introductionmentioning
confidence: 99%